Identification of immunosuppressive factors in retinoblastoma cell secretomes and aqueous humor from patients. Issue 3 (13th April 2022) - Cuadrado‐Vilanova, Maria; Liu, Jing; Paco, Sonia; Aschero, Rosario; Burgueño, Victor; Sirab, Nanor; Pascual‐Pasto, Guillem; Correa, Genoveva; Balaguer‐Lluna, Leire; Castillo‐Ecija, Helena; Perez‐Jaume, Sara; Muñoz‐Aznar, Oscar; et al.
Abstract: The microenvironment of retinoblastoma, the solid malignancy of the developing retina, is immunosuppressive. To study the interactions between tumor‐associated microglia/macrophages (TAMs) and tumor cells in retinoblastomas, we analyzed immunohistochemistry markers in 23 patient samples and characterized 105 secreted cytokines of 11 retinoblastoma cell models in culture. We detected profuse infiltration of CD163 + protumoral M2‐like polarized TAMs in eyes enucleated due to cancer progression. Previous treatment of patients increased the number of TAMs but did not affect M2‐like polarization. M2‐like microglia/macrophages were almost absent in five eyes obtained from children enucleated due to nontumoral causes. CD8 + tumor‐infiltrating lymphocytes (TILs) were moderately abundant in tumor eyes and very scarce in nontumoral ones. The expression of the immune checkpoint molecule PD‐L1 was absent in 95% of the tumor samples, which is concordant with the finding of FOXP3 + Tregs infiltrating tumors. We confirmed the pathology results using single‐cell transcriptome analysis of one tumor. We identified the cytokines extracellular matrix metalloproteinase inducer (EMMPRIN) and macrophage migration inhibitory factor (MIF), both with reported immunosuppressive activity, secreted at high levels in retinoblastoma primary cell cultures. Gene expression analysis of a large retinoblastoma cohort and single‐cell transcriptome analysis confirmed that MIF and EMMPRIN were significantly upregulated in retinoblastomas, which led us to quantify both proteins by immunoassays in liquid biopsies (aqueous humor obtained from more than 20 retinoblastoma patients). We found a significant increase in the concentration of MIF and EMMPRIN in cancer patients, compared to 12 noncancer ones. Finally, we showed that macrophages derived from peripheral blood mononuclear cells increased the expression of markers of M2‐like polarization upon exposure to retinoblastoma‐conditioned medium or recombinant MIF. Overall, our findings suggest that retinoblastoma cell secretions induce the protumoral phenotype of this tumor. Our results might have clinical impact in the fields of biomarkers and treatment. © 2022 The Pathological Society of Great Britain and Ireland.